2008
DOI: 10.4049/jimmunol.180.5.3148
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle-Associated Membrane Protein-8/Endobrevin Negatively Regulates Phagocytosis of Bacteria in Dendritic Cells

Abstract: Phagocytosis is a specialized mechanism used by mammalian cells, particularly the cells of the immune system, such as dendritic cells (DC) and macrophages, to protect the host against infection. The process involves a complex cascade of pathways, from the ligation of surface receptors of phagocytes with components of the microorganism’s surface, formation of phagosomes and subsequently phagolysosomes, to the eventual presentation of foreign Ags. Vesicle-associated membrane protein (VAMP)-8/endobrevin has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 33 publications
7
29
0
Order By: Relevance
“…However, Stx11 −/− BMDCs appeared not impaired in any of the activities investigated. Our results partially mirror previous findings that report that the ability of VTI1B-and VAMP8-deficient DCs to process antigen and stimulate the proliferation of CTLs was not reduced [18], although an inhibitory role for VAMP8, VTI1A and VTI1B was found in murine immature DC phagocytosis [24,25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Stx11 −/− BMDCs appeared not impaired in any of the activities investigated. Our results partially mirror previous findings that report that the ability of VTI1B-and VAMP8-deficient DCs to process antigen and stimulate the proliferation of CTLs was not reduced [18], although an inhibitory role for VAMP8, VTI1A and VTI1B was found in murine immature DC phagocytosis [24,25].…”
Section: Discussionsupporting
confidence: 91%
“…However, Stx11 −/− BMDCs appeared not impaired in any of the activities investigated. Our results partially mirror previous findings that report that the ability of VTI1B-and VAMP8-deficient DCs to process antigen and stimulate the proliferation of CTLs was not reduced [18], although an inhibitory role for VAMP8, VTI1A and VTI1B was found in murine immature DC phagocytosis [24,25].Next, we have reported that STX11 is constitutively expressed in BMMCs at the mRNA level and regulated upon LPS or IgE/Ag treatment. Again despite upregulation, STX11 deficiency does not affect BMMC degranulation activity based on LAMP-1/ CD107a and β-hexosaminidase measurements.…”
supporting
confidence: 91%
“…Thus, the efficacy of OVA uptake and cross-presentation on MHC class I molecules was not affected by a deficiency of vti1b or VAMP8. VAMP8 has been reported to negatively regulate phagocytosis in macrophages and DCs (33). Similarly, syntaxin-11 has been reported to act as a negative regulator of phagocytosis in human monocytes and macrophages (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that Ag processing is affected because it requires vesicular transport at several steps and VAMP8 has been described to regulate phagocytosis in macrophages and DCs (33). Thus, we added the OVA protein to the splenocyte cultures from the TCR-transgenic Vti1b-and Vamp8-deficient mice.…”
Section: The Processing Of Ags and The Stimulatory Capacity Of Dcs Armentioning
confidence: 99%
“…SNARE-dependent cytokine secretion from other innate immune cells, including NK cells and DCs, is not well characterized. NK target cell killing mediated by granzyme B secretion is dependent on VAMP-7 (68), and VAMP-8 is involved in phagosomal trafficking in DCs (44). NK cells also rely on REs to traffic cytokines to the cell surface (98).…”
Section: Macrophagesmentioning
confidence: 99%